2019
DOI: 10.13080/z-a.2019.106.003
|View full text |Cite
|
Sign up to set email alerts
|

Macro and trace elements in oat cultivars bred in Latvia

Abstract: The aim of the research was to quantify 13 macro and trace elements in different oat (Avena sativa L.) genotypes depending on the year of cultivation (2011, 2012 and 2013) and crop management practice (conventional or organic), agronomic practice (different N supply) and evaluate the risks regarding Cd, Pb, Cr, Ni, Cu, Zn and Al concentrations and nutritional aspects regarding K, Na, Ca, Mn, Mg, Fe, Cu, Zn and Cr concentrations in oat grain. Elements Cd, Pb, Cr, Ni and Al were detected by electrothermal atomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
2
2
1
Order By: Relevance
“…The contents of copper, manganese and zinc found for oat grains in this study are within the values of previous surveys developed for cereal grains [24] and oat grains [25][26][27][28].…”
Section: Influence Of Sewage Sludge Application On Cu Mn Zn Contentsupporting
confidence: 89%
See 1 more Smart Citation
“…The contents of copper, manganese and zinc found for oat grains in this study are within the values of previous surveys developed for cereal grains [24] and oat grains [25][26][27][28].…”
Section: Influence Of Sewage Sludge Application On Cu Mn Zn Contentsupporting
confidence: 89%
“…Cadmium contents for oat grains reported by other researchers are much lower than those evidenced in present study, respectively 0.0045-0.0550 mg/kg [27] and 0.008-0.023 mg/kg [28]. As reported by Brunetti et al [30], cadmium levels ranged from 0.03 to 0.1 mg/kg from wheat grains and below detection limit to 0.02 mg/kg for barley grains.…”
Section: Influence Of Sewage Sludge Application On Cadmium Cobalt Ancontrasting
confidence: 63%
“…Similar calcium levels were reported by Jakobsone et al for oat grains [31,32]. Del Coco et al found the same calcium levels in wheat grains [30].…”
Section: Influence Of Sewage Sludge Application On Ca and Mg Contentssupporting
confidence: 87%
“…(2016) was 112–120 mg/100 g and Özcan et al. (2017) was 202.5–225.3 mg/100 g Jakobsone et al. (2019) studied the macro and trace elements in oat cultivars bred in Latvia and they found that weather conditions (air temperature and rainfall) influence the amounts of calcium, potassium, sodium, and magnesium.…”
Section: Resultsmentioning
confidence: 99%